Exploitation of power and the exclusion of other knowers - Hannum, Dane Shade Brusuelas, author; Shockley, Ken, advisor; McShane, Katie, committee member; DeMirjyn, Maricela, committee member (Colorado State University. Libraries, 2019)
I argue that the relatively dominant political cultural and economic order of a given period produces, as a structural feature, relatively dominant epistemic frameworks that exclude certain methods of knowing. These methods of knowledge production are often represented by particular groups of knowers, and I argue that their exclusion is the result of the exploitation of an unjust power differential. The exclusion of particular forms of knowledge production and their representative groups is a problem with both epistemic and moral import. In my first chapter, I focus on presenting the claim that scientific inquiry and the production of knowledge is never neutral and is always embedded within a set of political and cultural conditions. I provide examples of cases in which the influence of relatively dominant groups on frameworks for knowledge has resulted in unjust exclusion of certain knowers, and modes of knowledge production. In my second chapter I focus on the connection between specific groups of knowers and specific methods of knowledge production. In particular, I focus on practice-based knowledge possessed by politically or culturally marginalized groups as forms of knowledge which have often been excluded from the dominant framework. I argue that when particular groups of knowers are excluded this is a problem with both epistemic and ethical import. In my third and final chapter, I identify the unjust exploitation of power differentials as the cause of both the epistemic and ethical issue of exclusion.
Keywords: science; epistemology